Jobs at Risk!? Effects of Automation of Jobs on Occupational Mobility - Alina Sorgner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
The paper investigates the relationship between the risk of automation of jobs and individual-level occupational mobility using a representative German household survey. The results suggest that expected occupational changes such as losing a job and demotion at the current place of employment, among others, are likely to be driven by the high occupation-specific risk of automation. However, switches to self-employment are more likely to occur from occupations with low risk of automation.
Keywords: J24; J62; L26; 330